Biogenic silica accumulation varies across tussock tundra plant functional type. (4th July 2017) - Carey, Joanna C.; Parker, Thomas C.; Fetcher, Ned; Tang, Jianwu
Abstract: Silica (SiO2 ) accumulation by terrestrial vegetation is an important component of the biological silica cycle because it improves overall plant fitness and influences export rates of silica from terrestrial to marine systems. However, most research on silica in plants has focused on agricultural and forested ecosystems, and knowledge of terrestrial silica cycling in the Arctic, as well as the potential impacts of climate change on the silica cycle is severely lacking. We quantified biogenic silica (BSi) accumulation in above and below‐ground portions of three moist acidic tundra (MAT) sites spanning a 300 km latitudinal gradient in central and northern Alaska, USA. We also examined plant silica accumulation across three main tundra types found in the Arctic (MAT, moist non‐acidic tundra and wet sedge tundra (WST)). Biogenic silica concentrations in live Eriophorum vaginatum, a tussock‐forming sedge that is the foundation species of tussock tundra, were not significantly ( p < .05) different across the three main sites. Concentrations of BSi in live above‐ground tissue were highest in the graminoid species (0.55 ± 0.07% BSi in sedges from WST, and 0.27 ± 0.01% in E. vaginatum across the three MAT sites). Both inter‐tussock tundra species and shrubs contained substantially lower BSi concentrations than E. vaginatum . Our results have implications for how shifts in vegetation cover associated with climatic warming may alter silica storage in tussock tundra vegetation. Our calculations suggest that shrub expansion via warming will increase BSi storage in Arctic land plants due to the higher biomass associated with shrub tundra, whereas conversion of tussock tundra to WST via permafrost thaw would produce the opposite effect in the terrestrial plant BSi pool. Such changes in the size of the terrestrial vegetation silica reservoir could have direct consequences for the rates and timing of silica delivery to receiving waters in the Arctic. A plain language summary is available for this article. Abstract : Plain Language Summary